The Effect of Organizational Culture and Work Environment on Organizational Commitment through Job Satisfaction - Nadiyah Urfa; Hairani Tarigan (Penerbit Goodwood, 2026)
Objective: To determine the influence of organizational culture and work environment on organizational commitment with job satisfaction as a mediating variable, along with high turnover rates due to low employee commitment. A quantitative approach was used with path analysis using the SmartPLS 4 statistical application. Methodology/approach: Quantitative approach was carried out by path analysis using the SmartPLS 4 statistical application. The sample consisted of 156 employees of Hangtuah Coffee and Toastery who were selected by purposive sampling. Results/findings: Results indicate that organizational culture and work environment positively affect job satisfaction. Culture also directly influences organizational commitment, while the work environment has no significant direct or indirect effect. Conclusions: Organizational culture and work environment boost job satisfaction, which enhances commitment. Culture directly affects commitment, while the work environment alone does not. Combining supportive culture with a positive work environment is essential to fully engage and retain employees. Limitations: Data collection is only at one point in time in January 2025, so it is not possible to observe changes in variables over time that could strengthen the results of the study. Contribution: The research model had high R² and Q² values and low SRMR, indicating good fit and predictive ability. The implications of this study help management in designing strategies to increase loyalty and reduce turnover by strengthening the organization's culture and creating a supportive work environment to increase employee satisfaction and commitment.